2007
DOI: 10.1016/j.jacc.2006.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Inflammation Evaluated by [18F]-Fluorodeoxyglucose Positron Emission Tomography Is Associated With the Metabolic Syndrome

Abstract: ObjectivesWe investigated factors for carotid artery inflammation by [ 18 F]-fluorodeoxyglucose (FDG) positron emission tomography (PET).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
174
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(196 citation statements)
references
References 21 publications
16
174
4
2
Order By: Relevance
“…After anecdotal reports, aortic FDG uptake in patients undergoing FDG-PET imaging for oncology staging was described in 2001 [41], and later noted as increasing with age [42], male sex and the presence of vascular risk factors [43][44][45]. In the first prospective clinical study, Rudd et al [46] imaged eight patients shortly after transient ischaemic attack (TIA) with FDG-PET and reported an FDG accumulation rate 27% higher in the symptomatic carotid compared to the contralateral asymptomatic side.…”
Section: Clinical Studies With Fdg-petmentioning
confidence: 99%
See 2 more Smart Citations
“…After anecdotal reports, aortic FDG uptake in patients undergoing FDG-PET imaging for oncology staging was described in 2001 [41], and later noted as increasing with age [42], male sex and the presence of vascular risk factors [43][44][45]. In the first prospective clinical study, Rudd et al [46] imaged eight patients shortly after transient ischaemic attack (TIA) with FDG-PET and reported an FDG accumulation rate 27% higher in the symptomatic carotid compared to the contralateral asymptomatic side.…”
Section: Clinical Studies With Fdg-petmentioning
confidence: 99%
“…This has proved important in the search for quantitative measures of inflammation that can be used to test the impact of new therapies. Uptake may be widespread [44,54], although especially affecting the carotid arteries and proximal aorta (Figs 1 and 2). This is consistent with the hypothesis that atherosclerosis is a generalized inflammatory condition.…”
Section: Clinical Studies With Fdg-petmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood chemistries were measured at our laboratory, using an enzyme-linked immunosorbent assay or an enzymatic assay method as described previously. 10 Glomerular filtration rate was estimated with the Modification of Diet in Renal Disease study equation modified with a Japanese coefficient. 11 Severity of coronary artery stenoses were evaluated by more than 2 experienced interventional cardiologists blinded to the p66 shc data, using quantitative coronary angiography.…”
Section: Data Collectionmentioning
confidence: 99%
“…14 18F-FDG uptake is associated with traditional cardiovascular risk factors, including age, male gender and metabolic syndrome, as well as inflammatory biomarkers. 15,16 Moreover, vascular 18F-FDG uptake is elevated in patients infected with human immunodeficiency virus, perhaps accounting for their increased cardiovascular event rate. [17][18][19] A retrospective review of vascular 18F-FDG uptake on PET scans performed in patients with cancer has demonstrated an association between 18F-FDG uptake and subsequent vascular events.…”
mentioning
confidence: 99%